2003
DOI: 10.1046/j.1600-0684.2003.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Saimiri breeding colony of the Pasteur Institute (French Guiana): development of a molecular typing method using a combination of nuclear and mitochondrial DNA markers

Abstract: Saimiri (Cebidae) groups a complex of species and subspecies, which present a large morphological plasticity. Genetic analysis is complicated by the absence of consensus on classification criteria and the paucity of molecular tools available for the genus. As the squirrel monkey is widely used in biomedical research, breeding centers have been established, but the genetic make up and diversity of many of the existing colonies is unknown precluding a rationale breeding policy. To develop a genetic typing strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…The means of annual percent values used in the deterministic model were found to be of the same order of magnitude as those reported in the literature for other squirrel monkey colonies [Lavergne et al, 2003;Rasmussen et al, 1980;Taub et al, 1978]. However, we have not come across comparative historical data in the form of probability distributions.…”
Section: Datasupporting
confidence: 63%
“…The means of annual percent values used in the deterministic model were found to be of the same order of magnitude as those reported in the literature for other squirrel monkey colonies [Lavergne et al, 2003;Rasmussen et al, 1980;Taub et al, 1978]. However, we have not come across comparative historical data in the form of probability distributions.…”
Section: Datasupporting
confidence: 63%
“…However, we need a fine-scale resolution of the genetic structure of Saimiri populations in the wild and in captivity to be able to track geographic origins and define genetic structure of captive populations. For example, Lavergne et al (2003) genotyped the colony of Saimiri of the Pasteur Institute in French Guyana via mitochondrial and microsatellite markers. They found 3 distinct mitochondrial lineages from the Saimiri boliviensis, S. sciureus and S. s. collinsi group and private microsatellite alleles that distinguished Bolivian specimens (S. boliviensis) from Guyanese (S. s. sciureus) and Brazilian animals (S. s. collinsi).…”
Section: Cytogenetic and Molecular Parametersmentioning
confidence: 99%
“…The gothic group includes S. sciureus, S. ustus, and S. oerstedii, whereas the roman group includes S. boliviensis and S. vanzolinii [Ingberman et al, 2008]. Several molecular approaches have been suggested to circumvent the problem of unknown geographic origin, based on allozyme and microsatellite polymorphisms as well as sequencing marker genes [Boinski & Cropp, 1999;Cropp & Boinski, 2000;Lavernge et al, 2003;Silva et al, 1993]. Recently, Osterholz et al [2008] identified a pattern with the Alu insertion, a short sequence of DNA at a particular chromosome site, for S. sciureus (Alu insert absent) and S. boliviensis (Alu insert present).…”
Section: Ecologymentioning
confidence: 99%